Agro-preneurial obstacles among students in the Faculty of Plantation and Agrotechnology, UiTM Pahang / Ilyani Azer ... [et al.] - Azer, Ilyani; Mohamad, Siti Aishah; Abdullah, Nur Suraya; Mustapha, Musramaini (Research Management Institute (RMI), 2014)
Most tertiary institutions offer entrepreneurial programmes and courses to the students. However, there appears to be a lot of challenges in maintaining the elements of business in the real world. This study highlights the obstacles in entrepreneurship among students from the Faculty of Plantation and Agrotechnology, Univeristi Teknologu MARA (UiTM) Pahang. The main objective is to explore the perceptions toward the obstacles in agro-preneurship among the respondents. The results pointed out that the students’ perceptions of lack of experience, finding the right partner, and lack of information are the main three obstacles in agro-preneurship. In addition, specific obstacles in agro-preneurship exist based on the student’s gender which is caused by different obstacles.